2018
DOI: 10.1007/s00268-018-4869-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognoses and Clinicopathological Characteristics for Hepatocellular Carcinoma Originating from the Caudate Lobe After Surgery

Abstract: 1Background: The aims were to evaluate the prognoses, and clinicopathological characteristics of 2 solitary hepatocellular carcinoma (HCC) originating from the caudate lobe (HCC-CL). 3 Methods:We analyzed 584 patients with a solitary tumor < 10 cm from January 1990 to November 4 2014. Patients were classified into a caudate lobe group (CL; n = 39) and a non-caudate lobe group 5 (NCL; n = 545). We investigated the prognoses and clinicopathological characteristics of solitary 6 HCC-CL. We compared the surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 30 publications
(33 reference statements)
0
19
0
Order By: Relevance
“…Several studies have reported various clinical results of surgical resection, including 3- and 5-year OS of 47–83% and 21–76%, respectively. 5 , 36 , 39 The reported OS rates with RFA or chemoembolization for HCC-CL varied as follows: 59–86.6% at 3 years, and 44–67.5% at 5 years, 19 , 40–43 which were similar to those after surgical resection. However, the tumor size > 2 cm and intrahepatic tumor number are associated with poor prognosis after ablation.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Several studies have reported various clinical results of surgical resection, including 3- and 5-year OS of 47–83% and 21–76%, respectively. 5 , 36 , 39 The reported OS rates with RFA or chemoembolization for HCC-CL varied as follows: 59–86.6% at 3 years, and 44–67.5% at 5 years, 19 , 40–43 which were similar to those after surgical resection. However, the tumor size > 2 cm and intrahepatic tumor number are associated with poor prognosis after ablation.…”
Section: Discussionmentioning
confidence: 83%
“…2,3 Cases of HCC originating in the caudate lobe (HCC-CL) are rare, with an incidence rate between 1.9% and 12.4%. [4][5][6][7] The implementation of surveillance programs for high-risk populations and advances in diagnostic imaging technology has increased the diagnosis rate of HCC-CL. 8,9 The surgical resection and percutaneous radiofrequency ablation (RFA) can be used as a curative treatment for HCC-CL.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatocellular carcinoma (HCC) is a common malignancy, with incidence and mortality rates ranking sixth and third in the world, respectively (1). Cases of HCC arising or involving the caudate lobe (HCC-CL) are relatively rare, and its incidence is reported to be between 1.9% and 12.4% (2)(3)(4)(5)(6)(7). Although the implementation of surveillance programs for high-risk populations and advances in imaging diagnostic technology have increased the diagnosis rate of HCC-CL (8,9), about 80% of patients have tumors that are unresectable owing to either severe hepatitis-related cirrhosis or tumor invasion of the intrahepatic vessels (10).…”
Section: Introductionmentioning
confidence: 99%